PI3K signaling promotes formation of lipid-laden foamy macrophages at the spinal cord injury site - Christine B. Ryan; James S. Choi; Brian Kang; Seth Herr; Claudia Pereira; Carlos T. Moraes; Hassan Al-Ali; Jae K. Lee (Neurobiology of Disease, 2024)
After spinal cord injury (SCI), infiltrating macrophages undergo excessive phagocytosis of myelin and cellular debris, forming lipid-laden foamy macrophages. To understand their role in the cellular pathology of SCI, investigation of the foamy macrophage phenotype in vitro revealed a pro-inflammatory profile, increased reactive oxygen species (ROS) production, and mitochondrial dysfunction. Bioinformatic analysis identified PI3K as a regulator of inflammation in foamy macrophages, and inhibition of this pathway decreased their lipid content, inflammatory cytokines, and ROS production. Macrophage-specific inhibition of PI3K using liposomes significantly decreased foamy macrophages at the injury site after a mid-thoracic contusive SCI in mice. RNA sequencing and in vitro analysis of foamy macrophages revealed increased autophagy and decreased phagocytosis after PI3K inhibition as potential mechanisms for reduced lipid accumulation. Together, our data suggest that the formation of pro-inflammatory foamy macrophages after SCI is due to the activation of PI3K signaling, which increases phagocytosis and decreases autophagy.